Relationship Among Economic Growth, Energy Consumption, CO Emission, and Urbanization: Evidence From MINT Countries - Jamiu Adetola Odugbesan; Husam Rjoub (SAGE Open, 2020)
This study aimed at examining the synergy among economic growth, carbon dioxide (CO 2 ) emissions, urbanization, and energy consumption in MINT (Mexico, Indonesia, Nigeria, and Turkey) countries. Yearly data from 1993 to 2017, which were sourced from World Bank Development Indicators, were employed, and the analysis was performed by employing the ARDL Bounds test approach. The findings from the study reveal that the energy–growth hypothesis that assumed unidirectional causality from energy consumption was true for Nigeria and Indonesia, whereas Mexico and Turkey followed the feedback hypothesis, which indicates a bidirectional relationship. Meanwhile, all the MINT countries show a long-run relationship from economic growth, energy consumption, and CO 2 emissions to urbanization. The study suggests that the policymakers in MINT countries should develop an energy conservation policy that will enhance the potential growth of their economy. More so, there is a need to promote green industries. Finally, to ensure sustainable urbanization in MINT countries, concerted efforts need to be made to ensure the reduction in the urbanization level, so as to ensure the sustainability of the urbanization, but without compromising the economic growth, through the formulation of policies that will ensure the decrease in CO 2 emissions to achieve quality environment.